Intracardiac therapy following emergency thoracotomy in the accident and emergency department: an experimental model. Issue 2 (June 1992) - Moulton, C; Pennycook, A; Crawford, R
Abstract : For a select group of patients with penetrating chest trauma, immediate thoracotomy in the accident and emergency department offers the only chance of survival. Foley catheters have been used to achieve haemostasis in cardiac wounds but are not widely used for intracardiac fluid and drug administration during resuscitation. In an anatomical model designed to assess this procedure an average flow rate of 275 ml min-1 was achieved. The equipment required is readily available and easily assembled.